2021
DOI: 10.1111/bjh.17447
|View full text |Cite
|
Sign up to set email alerts
|

Optimal duration of imatinib treatment/deep molecular response for treatment‐free remission after imatinib discontinuation from a Canadian tyrosine kinase inhibitor discontinuation trial

Abstract: Although total duration of tyrosine kinase inhibitor (TKI) therapy and of molecular response at 4 log reduction or deeper (MR4) correlates with treatment-free remission (TFR) success after TKI discontinuation, the optimal cut-off values of the duration remain unresolved. Thus, 131 patients were enrolled into the Canadian TKI discontinuation study. The molecular relapse-free survival (mRFS) was defined from imatinib discontinuation till molecular recurrence, that is, major molecular response (MMR) loss and/ or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The EURO-SKI trial documented that longer DMR durations were associated with an increased probability of TFR (41). The recent TRAD study further reported that one additional year of MR4.0 duration decreased the risk of TFR failure by 14.0% and proposed six years as the shortest imatinib duration (65). Several studies reported the depth of molecular response at the study baseline could predict TFR (22,25,32).…”
Section: Clinical Indicatorsmentioning
confidence: 99%
“…The EURO-SKI trial documented that longer DMR durations were associated with an increased probability of TFR (41). The recent TRAD study further reported that one additional year of MR4.0 duration decreased the risk of TFR failure by 14.0% and proposed six years as the shortest imatinib duration (65). Several studies reported the depth of molecular response at the study baseline could predict TFR (22,25,32).…”
Section: Clinical Indicatorsmentioning
confidence: 99%
“…Survival is like that of sex- and age-adjusted people without CML in Europe, but not in the US and certainly not in resource-poor countries [ 33 ]. Considerable data suggest people with CML achieving a stable deep molecular response (DMR; ≥MR 4 ; 4-log BCR::ABL1 transcript decrease from the standardized baseline, corresponding to a transcript level ≤0.01% on the International Scale) can discontinue therapy, about one-half of whom achieving TFR [ 34 49 ]. The clinical advantage of TFR over lifelong TKI-therapy is obvious, but the road to achieving this goal is not simple, cheap or rewarding for everyone.…”
Section: Are Current Recommendations For Tki-therapy Appropriate?mentioning
confidence: 99%
“…Expert consensus statements and clinical practice guidelines recommend >5 years of imatinib and >3 to 5 years of a 2G-TKI, with a response ≥ MR 4 for ≥2 years [ 2 , 7 9 , 38 , 44 , 46 , 48 , 49 ]. Convincing data supporting these recommendations are lacking [ 10 ].…”
Section: How Many People Can Successfully Discontinue Tki Therapy?mentioning
confidence: 99%
See 1 more Smart Citation
“… 115 , 143 , 144 , 146 , 147 Recent study by Kim et al proposed six years imatinib treatment and 4.5 years of MR 4 response as the optimal duration for starting TFR. 147 …”
Section: Introductionmentioning
confidence: 99%